Hi I'm reading this great book Foundations of Analysis by Edmund Landau, a really old book that aims to build the foundations of analysis from basic arithmetic.(adsbygoogle = window.adsbygoogle || []).push({});

I'm not that strong on proofing yet but am trying, here is my problem.

Using these 5 axioms for the Natural numbers;

[tex] I) \ 1 \in \mathbb{N}[/tex]

[tex]II) \ \forall \ x \ \exists \ x' \ : x' \ = \ x \ + \ 1[/tex]

[tex]III) \ x' \ \neq \ 1[/tex]

[tex]IV) \ if \ x' \ = \ y' \ then \ x \ = \ y[/tex]

[tex]V) \ \exists \ \mathbb{R} \ : \ \mathbb{N} \ \subset \ \mathbb{R} \ , \ with \ the \ following \ properties \ - \ i) \ 1 \ \in \ \mathbb{R}, \ ii) \ if \ x \ \in \ \mathbb{R} \ then \ x' \ \in \ \mathbb{R}[/tex]

I want to prove that x' ≠ x. It's the second theorem, the first being;

If x ≠ y then x' ≠ y'

which is proved by assuming x ≠ y and x' = y'

so we find a contradiction with axiomIVabove because x' = y' means x = y.

This is beautiful and understandable but in proving x' ≠ x the proof goes as follows,

By axiomsIandIIIabove,

i)1' ≠ 1 because 1' = 1 + 1.

so 1 belongs in R.

Then it says;

ii)If x ∈ R then x' ≠ x and by theorem 1 (x')' ≠ x' so x' ∈ R

This makes no sense to me, where did it come from

EDIT: I don't know why you can't use axiom II and just rearrange x' = x + 1 into x = x' - 1 to prove it

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Little Proof

**Physics Forums | Science Articles, Homework Help, Discussion**